Conference Review - Languages & The Media, 6th International Conference & Exhibition on Language Transfer in Audiovisual Media, October 25-27, 2006, Berlin - Christoffersen, Ellen (Language at Work - Bridging Theory and Practice, 2007)
The participants of the conference, which had as its theme “Free Access – Priceless Rights?”, were professionals involved in subtitling, voice-over or translation, language industry specialists, distributors of audiovisual media products, producers of media programmes, broadcasters, researchers and representatives of viewer organisations.